Association of hypertriglyceridemic waist-to-height ratio and its dynamic status with incident hypertension: the Rural Chinese Cohort Study. Issue 12 (December 2019) - Li, Quanman; Zhang, Dongdong; Guo, Chunmei; Zhou, Qionggui; Tian, Gang; Liu, Dechen; Chen, Xu; Liu, Leilei; Liu, Feiyan; Cheng, Cheng; Qie, Ranran; Han, Minghui; et al.
Abstract : Objective: We aimed to evaluate whether hypertriglyceridemic waist-to-height ratio (HWHtR) and its dynamic status was associated with hypertension (HTN). Methods: We examined data for 10 312 nonhypertensive participants aged at least 18 years from the Rural Chinese Cohort Study at the baseline examination who were followed until 2014 with a median follow-up of 6 years. HWHtR was defined by combined triglyceride level and waist-to-height ratio (WHtR). Multiple logistic regression models were used to examine the probability of incident HTN according to HWHtR and its transformation, estimating odds ratios (ORs) and 95% confidence intervals (CIs). Results: A total of 127 men and 225 women with high triglyceride level and high WHtR (HTHWH) had incident HTN during follow-up. After adjusting for potential confounders, the probability of HTN was increased with HTHWH for men [OR 1.49 (95% CI 1.01–2.20)] but this association was not significant for women [1.21 (0.88–1.66)]. The results of the sensitivity analyses were robust for men and women. The ORs were generally consistent on subgroup analysis by age, BMI, SBP and DBP for men. As compared with persistent normal triglyceride level and normal WHtR (NTNWH), the transformation from baseline NTNWH to follow-up HTHWH was associated with increased probability of HTN for men [OR 4.16 (95% CI 2.21–7.84)]. However, for women, the association of changed HWHtR from baseline to follow-up with probability of HTN was not significant for almost all transformation groups. Conclusion: HWHtR and its dynamic status was associated with incident HTN for rural Chinese men. From this cohort study, HWHtR may be an indicator for interventions aiming to reduce HTN among these men. Abstract : Supplemental Digital Content is available in the text